Analysis of Agricultural Sector Economic Potentials in Lebong Regency Bengkulu Province - Joti Pauzia; Bambang Sumantri; Ellys Yuliarti (Badan Penerbitan Fakultas Pertanian (BPFP), 2023)
Analysis of the Economic Potential of the Agricultural Sector in Lebong Regency, Bengkulu Province. The purpose of this research is to analyze the potential of the agricultural sector in Lebong Regency and identify the competitiveness of the agricultural sector in Lebong Regency. This study uses the LQ (Location Quotient) and Shift Share analysis methods to identify the agricultural sector in the development of the Lebong Regency. This study uses secondary data on the PDRB of the Lebong district and Bengkulu Province from 2017 to 2021. Based on the analysis of the food crops sub-sector and plantation crops sub-sector, these are the leading sub-sectors or the current base sub-sector. Analysis of the proportional growth component (KPP) shows that the estate crops sub-sector is the most advanced in Lebong Regency.